Manufaktur dan Analisa Kekuatan Tarik Komposit Hybrid Serat Glass/Carbon untuk Aplikasi Pembuatan Blade Turbin Savonius - Shomad, Muhammad Abdus; Yudhanto, Ferriawan; Anugrah, Rinasa Agistya (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2020)
Blade design and material selection for savonius turbines need to accurate to produce high power input. This research aims to make the most robust blade material by vacuum infusion manufactured. The hybrid laminate composite applied in the manufacture of Savonius turbine blades consists of woven carbon fiber with chopped strand mat glass fiber and woven glass fiber. The variations of fiber composition comprised of five layers, namely 5An (5 layers of woven glass fiber), 5Ac (5 layers of chopped strand mat glass fiber), 2C-3An (2 woven carbon fiber-3 woven glass), and 2C-3Ac (2 woven carbon fiber-3 chopped strand mat glass fiber). The results showed 2C-3An for the best variation of hybrid laminate composite with the tensile strength of 219 MPa, with the modulus of elasticity of 6.8 GPa and the smallest density was 1.21 g/cm3.